Conditions of regularity of a general differential boundary-value problem for improperly elliptic equations - Burskii, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
The Fredholm property and well-posedness of a general differential boundary-value problem for a general improperly elliptic equation are analyzed in a two-dimensional bounded domain with smooth boundary.